(untitled) (Journal Of Educational and Psychological Researches, 2023)
The study aims to identify the impact of the round-robin strategy on the logical thinking of fourth-year middle school students in chemistry. Two groups were employed: an experimental group consisted of (30) students who were taught according to the round-robin strategy, and the control group consisted of (30) students who were taught according to the traditional method. The researcher adopted the experimental design with partial control by preparing the visual thinking test tool, which consists of (20) multiple-choice items, it was applied as a post-test on the research sample. The result showed that there was a statistically significant difference in favor of the experimental group, which was taught according to the Round Robin strategy. Finally, the researcher came out with several recommendations and suggestions.